Premature seed germination induced by very-long-chain fatty acids causes jelly seed disorder in the mango (Mangifera indica L.) cultivar 'Amrapali' in India. Issue 2 (3rd March 2016) - Shivashankar, Seshadri; Sumathi, Manoharan; Singh, Hari Shankar
ABSTRACT: Jelly seed (JS) in 'Amrapali' mango ( Mangifera indica L.) is a physiological disorder, the cause of which has long remained obscure. The disorder is distinguished by the appearance of jelly-like tissue in the pulp adjoining the stone, although the fruit show no external symptoms. The objective of this study was to determine the causative factor inducing the JS disorder in 'Amrapali' mango. Studies showed, for the first time, that JS in 'Amrapali' mango arose at the start of germination-associated events in the seed of developing fruit. The trigger for premature seed germination originated from reduced synthesis of very-long-chain fatty acids (VLCFAs) in the seed of developing fruit. This then promoted the production of cytokinins, leading to the onset of premature germination-associated events in the seed. Consequently, a large increase in the activities of pectinolytic enzymes in JS pulp occurred that led to the rapid degradation of pectin and excessive softening of the pulp, to the consistency of jelly. The application of plant growth regulators to developing fruit showed that gibberellic acid (GA3 ) increased the incidence of JS, while paclobutrazol reduced the incidence of JS, confirming that the onset of early germination during fruit maturation and ripening played a primary role in the incidence of the JS disorder.